Numb Chin Syndrome: Atypical presentation of metastatic breast cancer - Britta L. Bureau MD; Jennifer M. Connelly MD; Paul E. Barkhaus MD; Ryan Brennan DO (RRNMF Neuromuscular Journal, 2023)
Introduction/Background: Numb chin syndrome (NCS) is an uncommon but known complication of cancer. Prompt recognition is imperative to directed treatment. In some instances, numb chin may be complicated by other findings. Case Report: A 53-year-old female with past medical history of estrogen receptor positive invasive ductal breast carcinoma underwent partial mastectomy, chemotherapy, and radiation. After 6 years remission, new lung and liver metastases occurred, and chemotherapy resumed. Imaging was negative. Eight weeks later, she developed left chin numbness followed by progressive difficulty retaining food and drink. Her left lower lip weakened. Neurological examination revealed left lower lip weakness (showing a “droop” with attempted smile). The area of decreased sensation to sharp touch had expanded from the left chin to the nasolabial fold. The remainder of her neurological examination was unremarkable. Contrast-enhanced MRI was repeated which revealed a 1.9 cm enhancing left parotid mass. Summary/Conclusion: NCS is defined as an ipsilateral loss of chin sensation. If there is no history of trauma or dental injury and especially if the presentation is atypical, then cancer is the most likely etiology. This case began as an uncomplicated NCS that rapidly expanded to involve a greater portion of the trigeminal nerve distribution, in addition to a branch of the facial nerve. Thus, each focal deficit was not the result of separate distal nerve lesions, but rather partial proximal cranial neuropathies at their parotid gland propinquity.